AB0025 Prevalence of MEFV gene mutations in apparently healthy populations in balkan and central european countries. (23rd January 2014) - Debeljak, M.; Toplak, N.; Abazi, N.; Kolnik, M.; Szabados, B.; Mulaosmanovic, V.; Constantin, T.; Kuzmanovska, D.; Avcin, T.
Abstract : Background: Familial Mediterranean Fever (FMF) is an autosomal-recessive disorder characterized by recurrent attacks of fever and serositis. It is common in eastern Mediterranean population. There are only few FMF patients in Slovenia, Republic of Macedonia, Hungary, Bosnia and Herzegovina and the mutation carrier rate in these countries is not known. So far, over 80 disease associated mutations have been identified in MEFV gene; the most common are M694V, V726A, M680I, E148Q and M694I. The distribution pattern of MEFV mutation along the Mediterranean Sea is not uniform; eastern populations have the highest number of carriers (20-39%) [1], whereas the number of carriers in western Mediterranean populations is considerably lower [2]. Objectives: The aim of this study was to determine the carrier rate in apparently healthy Slovenian, Macedonian, Bosnian and Hungarian populations. Methods: We screened 100 subjects from each population. Exon 10 was PCR amplified and screening was performed with dHPLC. All amplicons with detected nucleotide changes were subsequently sequenced with ABI Prism 310 Genetic analyzer. Amplicons of exon 2 were directly sequenced. Results: Heterozygous mutations were found in 4% of apparently healthy Hungarians, 7% of Slovenians, 8% of Bosnians and in 16% of apparently healthy Macedonians. Mutations found in Hungarian population were as follows: V726A (1), K695R (3). Mutations found in Slovenian population were: V726A (1), K695R (5) and E148Q (1). Mutations found in Bosnian population were: V726A (1), K695R (6) and F756C (1). Mutations found in Macedonian population were as follows: E148Q (8), K695R (7) and M694V (1). Conclusions: We found higher than expected carrier rate in all populations, from 4% to 16%. It is interesting to note that more than half (60%) of detected carriers in all analyzed populations has K695R mutation. References: Papadopoulos VP, Giaglis S, Mitroulis I, Ritis K. The population genetics of familial mediterranean fever: a meta-analysis study. Ann Hum Genet. 2008 Nov;72(Pt 6):752-61. Aldea A, Calafell F, Arόstegui JI, Lao O, Rius J, Plaza S, et al. The west side story: MEFV haplotype in Spanish FMF patients and controls, and evidence of high LD and a recombination "hot-spot" at the MEFV locus. Hum Mutat. 2004; 23: 399. Disclosure of Interest: None Declared